How pro-poor are participatory watershed management projects?: an Indian case study - Kurian, Mathew; Dietz, T. (International Water Management Institute, 2005)
This report draws on a survey and case study evidence from 28 watershed management groups in Haryana to argue that participatory watershed management projects need not necessarily safeguard the interests of poorer rural households.